PENGARUH IPM DAN PDRB TERHADAP JUMLAH PENDUDUK EKONOMI TINGKAT RENDAH (MISKIN) DI SUMATERA UTARA - Suryani Suryani; Sintaini Fi Sholiha; Muhammad Sendi; Purnama Ramadani Silalahi (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine how much influence the HDI and GRDP have on the poverty rate in North Sumatra in 2017-2021. The method used in this study is quantitative by using multiple regression analysis with time series data as the method of analysis. The results showed that partially the Human Development Index Variable has a positive and significant relationship to the poverty rate in North Sumatra in 2017-2021 while the GRDP Variable has a positive and significant relationship to the poverty rate in North Sumatra in 2017-2020. Simultaneously there is influence between the human development index variables and Gross Regional Domestic Product on poverty. Furthermore, the value of the coefficient of determination shows 99.2%